Sistem Informasi Online Fashion Outlet Berbasis Web Menggunakan CodeIgniter - Harjono (Politeknosains, 2018)
The purpose of this Final Project is to improve and simplify the system of recording, data storage and preparing reports for the payment of tuition fees and data membership at Fashion Outlet. This research uses observation method. In the field, the writer acts as an active trainer and treasurer at the Fashion Outlet. to conduct a systematic study of the symptoms that occur to obtain the required data in the writing of the Final Project. The result of this research is that it can be easy to run the computerized based system, in conveying the information to the needy and using the facility can be done without limitation of space and time, and with the use of this application, the process of recording data and making the report into faster, effective, accurate and better than ever.